SPECIAL CHARACTERISTICS OF AYBEK'S HISTORICAL NOVEL «SACRED BLOOD» IN YOUTH EDUCATION (Conference Zone, 2022)
The article scientifically studied Aybek's historical novel «Sacred Blood» and its significance for the education of modern youth. The memorial novel is remarkable in terms of language and artistic skill. In creating the image in the novel, the writer skillfully used the art of psychological analysis, the richness of the folk language.